Health Status of Children of Chepang and Other Communities of Nepal - Ghimire, MN (Journal of Advanced Academic Research, 2015)
Background: The study was conducted among the children and parents of Chepang community to know their health status in comparison with other communities. Chepang is an indigenous ethnic group living in Central and Southern Nepal especially in Chitawan, Gorkha and Dhading districts and also known as one of the isolated tribal groups of Nepal. They have their own language known as Chepang but is called Chyo-bang by the people themselves. The Chepang settlement is often on very steep land, unfertile and not easily accessible. Methods: The study was cross-sectional descriptive design. Simple random sampling technique was used to select the 38 children and their parents from the Brahmin/Chhetri, Ethnic groups, Chepang and Dalit. Result: Only 42% respondents had reported that they had visited hospital for checkups during the time of pregnancy. Among them only 11% Chepang had visited hospital. Similarly, 79% reported the use of iron tablets during the pregnancy and after post-delivery periods. In the same way, 95% reported that they had given birth to a child at home. In an average, 17% children of Chepang had better height, weight and thickness of arm than other communities' children. Conclusion: Chepang are found back in health seeking practices than the other communities. Cent percent mother had reported that they had given the birth of 1st baby before 20 years of her age. Though, health status of Chepang children found better than other communities' children. Journal of Advanced Academic Research Vol.1(1) 2014: 24-28